2013
DOI: 10.1245/s10434-013-3288-8
|View full text |Cite
|
Sign up to set email alerts
|

Negative Parafibromin Staining Predicts Malignant Behavior in Atypical Parathyroid Adenomas

Abstract: Although WHO criteria are essential to differentiate parathyroid carcinoma from benign tumors, the presence of negative PF staining in an atypical adenoma predicts outcome better, whereas PF-positive atypical adenomas do not recur and can be considered benign. PF-negative atypical adenomas have a low but real recurrence risk and should be considered tumors of low malignant potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 22 publications
1
73
0
3
Order By: Relevance
“…However, with recent developments in molecular pathology and ancillary tools, the classification of these borderline tumours has been greatly refined 153. When used in the appropriate clinical and pathological setting, ancillary biomarkers serve a crucial role in the distinction of malignancy in these borderline tumours, thereby enhancing the accuracy of the pathological examination 38 42 43 45 46 98 99 155 156 158–161…”
Section: Pathological Manifestations Of Hyperparathyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with recent developments in molecular pathology and ancillary tools, the classification of these borderline tumours has been greatly refined 153. When used in the appropriate clinical and pathological setting, ancillary biomarkers serve a crucial role in the distinction of malignancy in these borderline tumours, thereby enhancing the accuracy of the pathological examination 38 42 43 45 46 98 99 155 156 158–161…”
Section: Pathological Manifestations Of Hyperparathyroidismmentioning
confidence: 99%
“…Based on the currently available evidence and our own experiences , loss-of-expression of retinoblastoma protein (Rb), Bcl-2a, p27, parafibromin, mdm2 and APC, as well as increased MIB-1 (Ki67) proliferative index >5%, overexpression of p53 and positivity for galectin-3 (in the absence of multiglandular disease) favours a diagnosis of malignancy in a parathyroid neoplasm with worrisome histopathological features 31 33 38 42–46 49 87 98 99 141 153 155 156 158–164. In particular, the use of parafibromin immunostain (figure 8E) is very helpful to differentiate between parathyroid adenomas (intact nuclear and nucleolar parafibromin expression) and parathyroid carcinomas (complete loss of nuclear or nucleolar parafibromin expression) 38 42 43 46 98 99 153 156 159 161 162.…”
Section: Pathological Manifestations Of Hyperparathyroidismmentioning
confidence: 99%
“…In this study, the specificity of parafibromin staining would decrease to 63 % if only atypical adenoma was used as the control, while the pooled specificity was 95 % if other benign lesions were also included. Recently, it was reported that negative parafibromin staining might predict recurrence of PTCA as well as atypical adenomas [26]. The authors suggested that atypical adenoma with negative parafibromin staining should be treated as tumor with low malignant potential.…”
Section: Discussionmentioning
confidence: 99%
“…1. From 286 potentially relevant publications, a total of 10 studies were eligible for data extraction and analysis [15][16][17][23][24][25][26][27][28][29]. The characteristics of these included …”
Section: Eligible Articlesmentioning
confidence: 99%
“…В работе S. Kruijff и соавт. [19] рецидив ПГПТ документирован в 3,7% (2/53) случаев. Стоит отметить, что в данном исследовании возврат болез-ни был зафиксирован только в 10% (2/21) парафи-бромин-негативных образований.…”
Section: а бunclassified